Trilobatin Protects Against Aβ25–35-Induced Hippocampal HT22 Cells Apoptosis Through Mediating ROS/p38/Caspase 3-Dependent Pathway - Chen, Nana; Wang, Jiao; He, Yuqi; Xu, Yingshu; Zhang, Yuchuan; Gong, Qihai; Yu, Changyin; Gao, Jianmei (Frontiers in Pharmacology, 2020)
Emerging evidence reveals that an aberrant accumulation of β-amyloid (Aβ) is the main reason of Alzheimer’s disease (AD) pathogenesis. Thus, inhibition of Aβ-induced neurotoxicity may be promising therapeutic tactics to mitigate AD onset and advance. The development of agent candidates by cultured neurons against Aβ-induced cytotoxicity is widely accepted to be an efficient strategy to explore the drug for AD patients. Previously, we have revealed that trilobatin (TLB), a small molecule monomer, derives from Lithocarpus polystachyus Rehd, possessed antioxidative activities on hydrogen peroxide-induced oxidative injury in PC12 cells. The present study was designed to investigate the effects and the underlying mechanism of TLB on Aβ-induced injury in hippocampal HT22 cells. The results demonstrated that TLB attenuated Aβ25–35-induced HT22 cell death, as evidenced by MTT assay and LDH release. Furthermore, TLB dramatically mitigated cell death after Aβ25–35 insulted via decreasing the intracellular and mitochondrial ROS overproduction and restoring antioxidant enzyme activities, as well as suppressing apoptosis. Of note, Aβ25–35 triggered increase in ratio of Bax/Bcl-2, activation of caspase-3, phosphorylation of tau, JNK, p38 MAPK, and decrease in Sirt3 expression, whereas TLB reversed these changes. Intriguingly, TLB could directly bind to p38, as evidenced by molecular docking and p38 inhibitor. Taken together, the results reveal that TLB effectively protects against Aβ25–35-induced neuronal cell death via activating ROS/p38/caspase 3-dependent pathway. Our findings afford evidence for the potential development of TLB to hinder neuronal death during AD.